Badania dotyczące dzieciństw(a) – perspektywa praw dziecka - Ewa Jarosz (Problemy Wczesnej Edukacji)
Research concerning children and childhood has been developing on the background of the evolution of different narrations (discourses) about a child. After the Convention on the rights of the child, narrations on the children’s rights and then about child well-being and the quality of children’s life became the very meaningful. As a consequence, a new type of research on childhood has been developing which has some specific foundations as for the object and procedures used. In the paper an attempt to expose main methodological assumptions of the new paradigm is presented, the role of subjective treatment of children in research and some patterns of childhood studies. This paradigm is dedicated to pedagogues, especially social pedagogues, as the way of researching childhoods close to their perception of studies as socially engaged and as interdisciplinary in the spectrum of exploration.